An analysis method of local entropy changes from atomic fluctuations - Takafumi Ishii; Takashi Kojima; Yusuke Yasuda; Kazushi Fujimoto (PLoS ONE, 2026)
A macroscopic variable, entropy, stands as a key representation that reveals the relationship between internal structure and material properties of elastomer equipped with entropic elasticity. The entropy of network strand in cross-linked polymer structure is a critical factor for elucidating rubber elasticity. However, calculation of local entropy variation that characterize macroscopic properties has been challenging to date. In this study, we propose a method, based on molecular dynamics, that estimates the entropy of local polymer-network structure by calculating the number of states from atomic fluctuations in phase space. Our analysis of coarse-grained molecular dynamics simulations showed that the calculated entropy agrees qualitatively not only with thermodynamic principles but also with values obtained from thermodynamic integration and related approaches. Furthermore, we calculated the entropy of cross-linked polymeric structures, which extends its applicability to measurement of both the entropy of entire system and entropy change in the local structures.